Measuring the efficiency of mathematics teachers in the use of achievement measurement tools in the secondary stage in Makkah Al- Mukarramah - Al- Lehyani, Afaf Radi; Alotaibi, Engud Obaid (Journal of Educational and Psychological Sciences, 2020)
The study aimed to measure the efficiency of mathematics teachers in using achievement measurement tools at the secondary stage in the Holy City of Mecca, and used the descriptive analytical method on a sample of 60 female teachers from the sectors of the city of Makkah Al- Mukarramah, and a measure was used by the researcher, The interview method came from one of the most common methods for a parameter to use the measurement methods, and their mean is (4.40), The observation was the last method used by female teachers to measure the achievement of female students in mathematics with an average of (4,00), and there are no statistically significant differences between the parameters due to the qualification, There are statistically significant differences between the teachers in their use of measurement methods dating back to years of experience, and the differences were in favor of their experience higher.